Expression of the reversion-inducing cysteine-rich protein with Kazal motifs and matrix metalloproteinase-14 in neuroblastoma and the role in tumour metastasis - Dong, Qian (Blackwell Publishing Ltd, 2010)
Neuroblastoma is the most common malignant tumour in infancy; the reversion-inducing cysteine-rich protein with Kazal motifs gene (RECK) is a tumour suppressor gene. Previous studies show that RECK inhibits tumour invasion and metastasis through negative regulation of the matrix metalloproteinase (MMP)-2, MMP-9 and MMP-14. Therefore, we wanted to detect the expression of RECK and MMP-14 in neuroblastomas to assess the correlation between the expression levels of these proteins, and to investigate the roles in the metastasis and development of the tumour. PV-6000 immunohistochemistry method was used to detect the expression levels of RECK and MMP-14 in 36 samples of neuroblastoma tissue. Samples from paraffin wax-embedded specimens and the complete clinicopathological data of 36 neuroblastoma and 10 ganglioneuroma patients were collected. The rate of expression of the RECK protein in the neuroblastoma was low (16.7%). Furthermore, it reduced with the increase in the invasive depth and distant metastasis (P=0.015; P<0.05). The rate of expression of the MMP-14 protein in the neuroblastoma was high (58.3%) and increased with the increase in the extent of invasive depth and distant metastasis (P=0.002; P<0.05). The expression of the RECK protein correlated negatively with that of MMP-14 (r =−0.418; P<0.05). Low levels of the RECK protein are expressed in the neuroblastoma, while the MMP-14 protein is expressed at high levels. The RECK and MMP-14 proteins may serve as markers in the estimation of the extent of metastasis and dissemination of the neuroblastoma.